2018
DOI: 10.15244/pjoes/75806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Habitat Complexity on Body Size of Two Spider Species, Alopecosa cuneata and A. pulverulenta (Araneae, Lycosidae), in River Valley Grasslands

Abstract: Many studies have shown that vegetation structure and habitat complexity affect taxonomic composition, functional diversity, and the number of individuals in spider assemblages. These factors also affect spider body size, but mechanisms responsible for that are still not well understood. In our research, we examined the relationship between the body size of spiders from two species -Alopecosa cuneata and A. pulverulenta -and environmental factors such as habitat type and habitat complexity. Our research was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Although we have not measured the size of adults across elevation, it is reasonable to predict that the size of ectotherms increases in colder conditions because individuals spend longer time growing (Angilletta et al, 2004;Valenzuela-Sánchez et al, 2015). Many studies have shown that several others factors affect spider body size such as predators being selective in their choice of prey, habitat complexity, and nutritional quality (Stańska, Stański, 2017;Stańska et al, 2018). Further investigations on the complexity of mechanisms that are responsible for this difference in body size are needed.…”
Section: Discussionmentioning
confidence: 94%
“…Although we have not measured the size of adults across elevation, it is reasonable to predict that the size of ectotherms increases in colder conditions because individuals spend longer time growing (Angilletta et al, 2004;Valenzuela-Sánchez et al, 2015). Many studies have shown that several others factors affect spider body size such as predators being selective in their choice of prey, habitat complexity, and nutritional quality (Stańska, Stański, 2017;Stańska et al, 2018). Further investigations on the complexity of mechanisms that are responsible for this difference in body size are needed.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding environmental heterogeneity and niche‐related processes, for example, the existence of fjords in high‐latitude regions at the South Pacific coast of Chile could be seen as a mechanism generating broader environmental biotopes where more species could fill up their niches for near‐coast marine organisms (Valdovinos et al 2003, Kiel and Nielsen 2010). This is because fjords, as spatially complex habitats, offer ample topographic relief and water depth ranges, availability of refugia (Kiel and Nielsen 2010) and a wide variety of environmental conditions (González‐Wevar et al 2011, Buhl‐Mortensen et al 2012, Stańska et al 2018). As a result, fjords can increase biodiversity and contribute to the formation of inverse latitudinal gradients in taxonomic and functional diversity (Santelices and Meneses 2000, Kiel and Nielsen 2010, Rivadeneira et al 2011, Mannion et al 2014, Moreno et al 2021).…”
Section: Introductionmentioning
confidence: 99%